Implementation of Administrative Data in the Production of Official Statistical Information in the Field of Public-Legal Relations - T. KHARABARA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The article examines the issue of statistics on the resolution of public legal disputes and the possibility of its implementation in the production of official statistics. The problem of the formation of statistical reporting by the judicial bodies of Ukraine in the field of public-legalrelations as administrative data is considered. Methodological regulations on the organization of state statistical surveillance on the consideration of cases of administrative offenses and persons brought to administrative responsibility in Ukraine were analyzed. It was established that the existing tools for committing administrative offenses do not reflect the current state and dynamics. Conclusions were drawn on the relevance of developing and approving such methodological provisions to replace those that have lost their validity.Particular attention is focused on the study of the experience of the Federal Republic of Germany in the field of administrative proceedings, in particular, the methodology of statistical observation of administrative proceedings, introduced by the Federal Statistical Service of the country, is considered. The regulatory framework, on the basis of which the statistical observation of the resolution of public legal disputes by administrative courts functions in the Federal Republic of Germany, is considered. A conclusion was formed about the expediency of borrowing similar experience and introducing similar statistical observation in Ukraine.The research substantiates the need to develop methodological provisions for the new state statistical observation “Execution of administrative proceedings”, which will contribute to ensuring access and transparency to indicators of the procedural activity of administrative courts, reflecting the problems of law enforcement practice and the effectiveness of the judicial form of protection against violations committed by state authorities.